Episodic remagnetizations related to tectonic events and their consequences for the South America polar wander path - Font, E.; Rapalini, Augusto Ernesto; Tomezzoli, Renata Nela; Trindade, R. I. F.; Tovher, E. (Geological Society, London, Special Publications)
The South American record of remagnetizations is linked to specific events of its tectonic history stretching back to Precambrian times. At the Ediacaran-Cambrian time interval (570-500 Ma), the final stages of the western Gondwana assemblage led to remagnetization of Neoproterozoic carbonates within the São Francisco-Congo Craton and at the border of the Amazon Craton, along the Araguaia-Paraguay-Pampean Belt. From the late Permian to early Triassic, the San Rafaelic orogeny and the emplacement of the Choiyoi magmatic province was responsible for widespread remagnetizations in Argentina and Uruguay. Cretaceous remagnetization has also been documented in Brazil and interpreted to result from magmatism and fault reactivations linked to the opening of the South Atlantic Ocean. We present a review of these widespread remagnetization events principally based on palaeomagnetic data and, when available, on rock magnetic and radiogenic isotope age data. This study gives an overview of the geographical distribution of the remagnetization events in South America, and provides important clues to better understand the geodynamic evolution of the South American plate at these times. In addition, magnetic mineralogy data for the different case studies presented here constrain the physical-chemical mechanisms that led to partial or total resetting of magnetic remanences in sedimentary rocks. Fil: Font, E. Universidade de Lisboa. Faculdade de Ciências; Brasil Fil: Rapalini, Augusto Ernesto. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Geología. Instituto de Geofísica "Daniel Valencio"; Argentina Fil: Tomezzoli, Renata Nela. Consejo ...